TXNIP Participated in NLRP3-Mediated Inflammation in a Rat Model of Cervical Spondylotic Myelopathy - Liu P; Li X; Liu J; Zhang H; You Z; Zhang J (Dove Medical Press, 2022)
Peisheng Liu,1,* Xiaofeng Li,1,* Jing Liu,2 Hengjia Zhang,1 Zhitao You,1 Jianfeng Zhang1 1Department of Spinal Surgery, Yantaishan Hospital, Yantai, People's Republic of China; 2Basic Department, Yantai Vocational College, Yantai, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianfeng Zhang, Department of Spinal Surgery, Yantaishan Hospital, No. 10087, Keji Avenue, Laishan District, Yantai, People's Republic of China, Tel +86-13780921732, Email zhangjfdoctor@126.comBackground: Cervical spondylotic myelopathy (CSM) is a spinal cord disease caused by cervical disc degeneration and related pathological changes. Cervical spondylotic myelopathy may result from inflammation responses and neuronal damage. Thioredoxin-interacting protein (TXNIP)/NOD-like receptor protein 3 (NLRP3) signaling promotes inflammation. However, the effects of TXNIP/NLRP3 on the pathogenesis of CSM have not been reported.Methods: A rat model of chronic cervical cord compression was established to observe changes in the levels of of TNXIP/NeuN and NLRP3/NeuN expression in the damaged anterior horn of the spinal cord following progression of CSM. Rats were injected with TXNIP small interfering RNA (siRNA) and scrambled control to determine the effects of TXNIP inhibition on NLRP3-mediated inflammation in rats with CSM. Behaviors effects and the expression of NLRP3 and pro-caspase-1 in the damaged spinal cord were evaluated.Results: The expression levels of TXNIP and NLRP3 were significantly increased in the damaged anterior horn of the spinal cord following CSM. Injection of TXNIP siRNA significantly improved behavioral measures and decreased apoptosis in the damaged anterior horn of spinal cord. Furthermore, the levels of NLRP3 and pro-caspase-1 in the lesioned area were reduced by the TXNIP siRNA injection.Conclusion: Thioredoxin-interacting protein participated in NLRP3 mediated inflammation in a rat model of CSM, which indicated that TXNIP may be a potential therapeutic target in improving CSM.Keywords: neuroinflammation, TXNIP/NLRP3, spinal cord dysfunction, pro-caspase-1